The book of lost things ebook The book of lost things: mister max 1. - Voigt, Cynthia (Mister Max, 2013)
Max's parents are missing. They are actors, and thus unpredictable, but sailing away, leaving Max with only a cryptic note, is unusual even for them. Did they intend  to leave him behind? Have they been kidnapped?  Until he can figure it out, Max feels it's safer to keep a low profile. Hiding out is no problem for a child of the theater. Max has played many roles, he can be whoever he needs to be to blend in. But finding a job is tricky, no matter what costume he dons. Ironically, it turns out Max has a talent for finding things. He finds a runaway child, a stray dog, a missing heirloom, a lost love. . . . So is he a finder? A detective? No, it's more. Max finds a way to solve people's problems—he engineers better outcomes for them. He becomes Mister Max,  Solutioneer.    Now if only he could find a solution to his own problems . . .